Mapping Netizen Responses on Kompas.com Regarding Nickel Mining in Raja Ampat - Dhia Khinanti Audi Priyono; Moch. Fuad Nasvian (International Journal Labs, 2025)
Mining schemes are often promised to bring prosperity and progress, but on the other hand, mining activities that encroach on most of Indonesia's landscape cause environmental pollution, ecological degradation, and social crises that worsen Indonesia's condition. This study analyzes public responses to nickel mining in Raja Ampat through netizen comments on the Kompas.com YouTube platform. This research uses exploratory computational content analysis (CATA) with Voyant tools. The data comes from comments on 58 Kompas.com YouTube videos with titles related to